Reconstruction of an order of derivative and a source term in a fractional diffusion equation from final measurements. (17th January 2018) - Janno, Jaan; Kinash, Nataliia
Abstract: An inverse problem to recover a space-dependent factor of a source term and an order of a time derivative in a fractional diffusion equation from final data is considered. The uniqueness and stability of the solution to this problem is proved. A direct method to regularize the problem is proposed.